2020
DOI: 10.1029/2020jd032975
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Dynamics of a Saharan Dust Outbreak Over Mindelo, Cape Verde Islands, Preceded by Rossby Wave Breaking: Multiscale Observational Analyses and Simulations

Abstract: We investigate the synoptic precursors to the Harmattan wind and dust frontogenesis during the high impact Saharan dust outbreak over the Cape Verde Islands on 13 November 2017. We employ multiscale observations and the Weather Research and Forecasting model Coupled with Chemistry simulations. The analyses indicate that the dust storm was initiated on the lee side of the Saharan Atlas Mountains (SAM) in Algeria on 10 November 2017. This dust storm was associated with a double Rossby wave break linked through n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 46 publications
(67 reference statements)
0
12
0
Order By: Relevance
“…Next, we identified cold pools as a mechanism for producing high wind speeds and dust emission and transport in the region. Cold pools generated by orographic precipitation (e.g., Gläser et al., 2012; Knippertz et al., 2007) or frontal passage (Dhital et al., 2020) have been shown to generate strong winds and dust storms in Northern Africa, and thus this work shows that those same processes are also important in the small and closed Salton Basin. We also corroborated several results from numerical modeling studies of dust within a density current (Huang et al., 2018; Solomos et al., 2012), including that dust mixing outside the density current primarily takes place within the current head, that the peak in dust emission occurs after head passage, and that variations in height in the dust‐pristine sky interface are due to K‐H instability and billows.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Next, we identified cold pools as a mechanism for producing high wind speeds and dust emission and transport in the region. Cold pools generated by orographic precipitation (e.g., Gläser et al., 2012; Knippertz et al., 2007) or frontal passage (Dhital et al., 2020) have been shown to generate strong winds and dust storms in Northern Africa, and thus this work shows that those same processes are also important in the small and closed Salton Basin. We also corroborated several results from numerical modeling studies of dust within a density current (Huang et al., 2018; Solomos et al., 2012), including that dust mixing outside the density current primarily takes place within the current head, that the peak in dust emission occurs after head passage, and that variations in height in the dust‐pristine sky interface are due to K‐H instability and billows.…”
Section: Discussionmentioning
confidence: 62%
“…However, a series of images from the RoundShot camera looking west from camera's location (Figure 2) do not show obvious regions of widespread virga (Figure S1 in Supporting Information S1), which could be due to the 10-min resolution of the imagery. Given the available evidence, we cannot conclusively rule out the possibility that the density current feature described in the subsequent section was generated in association with cold post-frontal downslope flow (Dhital et al, 2020;Karyampudi et al, 1995).…”
Section: Synoptic Situation and Upstream Environmentmentioning
confidence: 89%
See 1 more Smart Citation
“…Case studies of North African dust storms with strong impact over southern Europe found a common large-scale upper-level precursor (a double Rossby wave breaking process) developing 5–10 days prior to dust storm formation. Using this precursor signal as an indicator might provide early warnings of high-impact North African dust outbreaks over southern Europe at lead times of 5–10 days 20 , 21 . In general, the predictive lead time is limited to several days.…”
Section: Introductionmentioning
confidence: 99%
“…Since RWB modifies dynamic conditions of the atmosphere, it gives rise to several weather events including not only the EREs (Antokhina et al, 2021;Martius and Rivière, 2016;Moore et al, 2019;Vellore et al, 2016;Vries., 2021), but also cold/heat waves (Ali et al, 2022;Song & Wu, 2021), anomalous changes in tropospheric ozone concentrations (Isotta et al, 2008;Zhang et al, 2022), and dust transport (Dhital et al, 2020;Nielsen-Gammon, 2001;Orza et al, 2020). Recently, Moore et al (2019) documented a strong correlation between the ERE and RWB in the United States which was found to be associated with strong warm air advection, tropical moisture export, and a warm conveyor belt supported by baroclinically forced ascent.…”
mentioning
confidence: 99%